2020
DOI: 10.4209/aaqr.2019.09.0458
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Marine Aerosols in a South Mediterranean Coastal Area Located in Bou Ismaïl, Algeria

Abstract: Daily concentrations of inorganic and organic compounds associated with PM 10 , i.e., atmospheric particulate matter with aerodynamic diameter of less than 10 µm, was determined at the south Mediterranean coastal area located in Bou Ismaïl, 40 km west of the Algiers city area in Algeria. From September 2011 to January 2012, chemical characterization of aerosol particles comprising water-soluble ions (WSI), trace metals, carbonaceous aerosols, the anhydrosugars levoglucosan and arabitol, dicarboxylic acids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 79 publications
(131 reference statements)
1
11
0
Order By: Relevance
“…Two factors cloud be responsible for the high nitrate concentration recorded at AMV. Firstly, the mineral dust particles present in the Middle Atlas region contain calcium carbonates (calcite and dolomite), which can react with nitric acid gas in the atmosphere to form nitrate salts (Krueger et al, 2004;Khrissi et al, 2018). Second, the difference could be explained by long-range transport of polluted air mass from MCE and ACE, which enhanced the nitrate concentration.…”
Section: Ammonium Nitrate and Sulfatementioning
confidence: 99%
See 1 more Smart Citation
“…Two factors cloud be responsible for the high nitrate concentration recorded at AMV. Firstly, the mineral dust particles present in the Middle Atlas region contain calcium carbonates (calcite and dolomite), which can react with nitric acid gas in the atmosphere to form nitrate salts (Krueger et al, 2004;Khrissi et al, 2018). Second, the difference could be explained by long-range transport of polluted air mass from MCE and ACE, which enhanced the nitrate concentration.…”
Section: Ammonium Nitrate and Sulfatementioning
confidence: 99%
“…Two main sources are known to be responsible for the presence of n-alkane-2-one in the air: incomplete combustion and in situ microbial α oxidation of the carbon chain (Khedidji et al, 2020). The first source often creates n-alkane-2one with a predominance of odd-numbered carbon atoms; on the other hand, the last source gives rise to the opposite.…”
Section: N-alkan-2-onesmentioning
confidence: 99%
“…Their study analyzed the chemical compositions of aerosols between May 2011 and April 2012, suggesting that carbonaceous aerosols were mainly related to local emissions by traffic than transported over long distances. Khedidji et al ( 2020 ) reported lower contributions of OC (3.1 μg m −3 ) and EC (1.2 μg m −3 ) from September 2011 to January 2012 in Bou Ismaïl, Algeria, which is located in the south Mediterranean coastal area. Similarly to Fez, OC (3.72 μg m −3 ) and EC (1.36 μg m −3 ) mean concentrations were also significantly elevated in October (Khedidji et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Parent PAH ratios are widely used to identify combustionderived PAHs (Khedidji et al, 2020;Szabó et al, 2015;Tobiszewski and Namieśnik, 2012), although some of them are photochemically degraded in the atmosphere (Yunker et al, 2002). Additionally, n alkanes are employed as markers of fossil fuel or vegetation contributions to PM 2.5 .…”
Section: Component Equation Referencementioning
confidence: 99%